Nghiên cứu khám phá về chuyển đổi số của các doanh nghiệp Việt Nam trong khu vực xuất nhập khẩu - Nguyễn Kim, Thảo; Lê Thị Hồng, Minh (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2022)
The future prospects of Vietnam’s economic development are directly linked to the economy’s capacity to digitally change, with the digital transformation ability of the import-export sector playing a key role. However, there are several barriers to the use of digital technology in import-export units, and proper policies are required to overcome these hurdles and establish favorable conditions for the promotion of digital transformation in the region. In-depth interviews with practitioners at 10 Vietnamese import and export companies were used to gather data. The findings reveal some key enablers of digital transformations at these firms and factors affecting their success of digital transformation process. Implications to promote digital transformation in import-export enterprises in Vietnam are made at multiple levels for policymakers, managers, and individuals.